THE FEASIBILITY OF USING MODERN SOFTWARE FOR THREE-DIMENSIONAL MODELING IN THE JEWELRY INDUSTRY - RUBANKA, MYKOLA; VYNNYCHUK, MARIIA; VYDOLOB, DMYTRO; POLISHCHUK, OLEH; KAMENIEV, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article considers the features of the jewelry designer`s work at the design stage of the creation of jewelry. The feasibility of using the Rhinoceros 3D modern software for three-dimensional NURBS modeling is proved. The scientific novelty consists in the development of engineering methods of jewelry design. The most common computer programs for three-dimensional modeling of various levels of complexity are listed. A complex of general scientific approaches has been used to conduct the research, namely the visual-analytical approach, the system-informational approach, modern methods of analysis of mechanical systems, analysis of scientific literature as well as the method of classifications. The most important factors that directly affect the process of creating jewelry are singled out. The algorithm for creating a three-dimensional model of a single-profile ring with engraving by using the Rhinoceros 3D software is proposed and its main stages are characterized. Certain recommendations for the effective use of the Rhinoceros 3D software for three-dimensional NURBS modeling in the jewelry industry are formulated.